Study the role of personal factors on life satisfaction of nurses employed in ‎hospitals affiliated to Guilan University of Medical Sciences - Nastaran Mirfarhadi; Saghi Mousavi; Rasool Tabari; Ehsan Kazemnejhad leili (Guilan University of Medical Sciences, 2011)
Introduction: Life satisfaction is primier purpose of human s life and it provides sufficient ‎basis for progress and confident basis to achieve higher levels. On the other hand, life ‎satisfaction brings out successes. Many studies have shown different factors such as ‎individual factors can affect life satisfaction. In attention to the role of nursing as key member ‎of healthcare, identifying effective factors on their satisfaction can have a direct effect on the ‎quality of healthcare and also on the society.‎ Objective: This study was done to determine the role of personal factors on life satisfaction of ‎nurses employed in hospitals affiliated to Guilan University of Medical Sciences.‎ Methods: In this descriptive-correlated study, ‎‏309‏‎ nurses in eight educational centers in ‎Guilan University of Medical Sciences were selected by stratified sampling and were ‎investigated by a two part questionnaire including life satisfaction index and personal ‎demographics. Data were analyzed using descriptive and inferential statistics tests (Multiple ‎Regression, Spearman, Mann-Whitney U test and Kruskal-Wallis) with SPSS ‎‏16‏‎ software. ‎ Results: Findings of this study shows most of research cases (‎‏79.6%‏‎) are satisfied with their ‎lives and there is a significant relation between life satisfactions with gender (p<‎‏0.01‏‎) and ‎average monthly income (p<‎‏0.008‏‎) while there was no significant relation between life ‎satisfaction with other personal factors (age, level of education, type of employment, position, ‎work experience, ward working, work experience in present ward and work shift). ‎ Conclusion: In attention to findings of study which shows a relative significance of personal ‎factors (gender and mean monthly income) on nurses, life satisfaction, it seems that a plan to ‎increase income can promote nurses life satisfaction.‎